Public services management and co-production in multi-level governance setting - Sicilia, Mariafrancesca et al (2016)
From a normative stance, co-production has been recommended at all stages of the public service cycle. However, previous empirical studies on co-production have neglected the question of how to make this happen. Moreover, little attention has been paid to how co-production might occur in multi-level governance settings. The aim of this article is to fill these gaps, identifying triggers and organizational and managerial issues that could support the adoption of co-production in multi-level governance settings. The empirical analysis is based on a case study of services for autistic children. The findings highlight that co-production was prompted by inter-organizational arrangements and that trust-building among the actors played a pivotal role in nurturing a co-production approach. - Reproduced.
Keywords: Public administration